Formação continuada de professores para o PROEJA: a realidade do Instituto Federal de Educação, Ciência e Tecnologia do Pará- IFPA - Lira, Carla Andreza Amaral Lopes (2011)
On account of the increasing discussion about the teacher formation, this present study is the result of the research of the Master’s Course on Education, in the branch of study Teacher Formation. The main goal of this work is to investigate if the former students of the Especialização PROEJA (Programa Nacional de Integração da Educação Profissional com a Educação Básica, na modalidade EJA), offered by IFPA are using the knowledge acquired in the course in their pedagogical practice. Also, is those students are stimulating and acting as multipliers of the Program ideas in the Institution. The specific objectives are: to contextualize the implementation of PROEJA at a national level and at IFPA, posing the political moment before and after its posing the political moment before and after its effectuation; to describe and conceptualize the proposition of the integrated curriculum for the PROEJA, seeking to understand and analize which are the difficulties and possibilities found by the teachers and managers when considering the accomplishment of that curriculum; to identify and examine the importance of the specialization, of the continuous teacher formation on the understanding and actuation of the integrated curriculum conceived by the PROEJA. The post-graduation course was presented by the IFPA from 2006 to 2009, financed exclusively by SETEC/MEC and aimed to train professionals with abilities to act on the development of strategies and on the establishment of creative forms of the learning and teaching activities. Also, the course had the goal of foreseeing in a pro-active way the necessary conditions and possible alternatives for the adequate development of the pedagogical practice, aiming the student’s learning. The teacher formation will be considered in this work, as well as the two reforms of the Professional and Technological Education, in 1996 and 2010; a brief summary of curriculum will be done besides the complete political and social context from which the PROEJA arose in Brazil and the post-graduation course in the IFPA. The research was carried out with teachers and administrative workers from the IFPA-campus Belém, in a total of 10 subjects who finished the course from 2006 to 2008. The chosen method was the Construtivist one, using the Hermeneutic Dialectic Circle technique (HDC), proposed in 1989 by Guba and Lincoln, that aims a joint discussion and construction among the subjects of the research and the interviewer, through talking and thinking, seeking what the mentioned authors call consent (when it is possible). This methodology echoes the Positivist method, that works with the duality subject-object, which in the Construtivist methodology is built from the reciprocity relationship between the observer and the observed, among the authors of the research. We dealt with authors who bring about the discussion on the Professional education, such as Marise Ramos, Dante Henrique Moura, Maria Ciavatta, and some others who work on the teacher formation theme as Selma Garrido Pimenta, Maurice Tardif. Institutional documents like reports and pedagogical course propositions were used. The final analysis pointed out that the subjects who were interviewed succeeded in practicing the knowledge acquired in the post graduation course. Thus, it was possible to achieve the general objective of this study.